Improving Time to Antibiotics for Pediatric Oncology Patients With Fever and Suspected Neutropenia by Applying Lean Principles. Issue 11 (November 2020) - Geerlinks, Ashley V.; Digout, Carol; Bernstein, Mark; Chan, Andrew; MacPhee, Shannon; Pambrun, Chantale; Gallant, Gloria; Wyatt, Lois; Fernandez, Conrad V.; Price, Victoria E.
Abstract : Background: Fever in the setting of neutropenia is a potentially life-threatening complication of cancer treatment. A time of less than 60 minutes from presentation to antibiotic administration is therefore recommended. Objective: To use Lean Six Sigma methodology, a quality improvement initiative, to improve time to antibiotics (TTA) for children with chemotherapy-induced febrile neutropenia presenting to the emergency department. Methods: Lean Six Sigma is a quality improvement method that engages all impacted stakeholders and focuses on streamlining the process by removing process wastes. Stakeholders identified multiple process wastes in an in-depth study of 49 fever episodes in patients attending a tertiary care pediatric hospital, including patients waiting to be registered, waiting for laboratory technicians, delay in accessing central venous access device, waiting for absolute neutrophil count, and delayed antibiotics orders. We implemented multiple solutions: engaging patients in the process through predischarge tours of the emergency department, home application of topical anesthetic, nurse-initiated pathway, early access of central venous access device for all blood work, and planned antibiotic administration no later than 45 minutes after triage. We prospectively determined the impact of these interventions on TTA. Results: The TTA significantly improved to a median of 59 minutes (interquartile range, 38.5–77.5 minutes) compared with the baseline of 99 minutes (interquartile range, 72.0–132.0 minutes; P < 0.0001). Conclusions: Lean methodology effectively identifies barriers and provides solutions to remove barriers and improve administration of antibiotics in febrile oncology patients. These can be widely applied, including in smaller institutions with minimal increased utilization of resources.